MaHaKeTang: An Innovative Method for Learning How to Style a Ukel Tekuk Bun - Wahjuningsih, Anik; Supriyono, Supriyono; Dayati, Umi; Hardika, Hardika (Departement of Nonformal Education, Graduate Scholl of Universitas Negeri Yogyakarta, 2024)
Abstract: Non-formal educational institutions, such as bridal makeup courses, must innovate to provide adaptive learning for students in theory and practice to meet the market demand. This study used a qualitative phenomenological approach to reveal the process of knowledge transfer related to local wisdom, especially the implemented MaHaKeTang learning technique at Imam Mandiri Blitar Course and Training Institute (LKP) and has successfully facilitated its graduates for their employment and starting their businesses. This study involved 12 participants, including the founders, instructors, alumni, and students of LKP Imam Mandiri. The data were collected through interviews and observations and analyzed using descriptive and quantitative methods. This study found that the MaHaKeTang technique is implemented by synergizing the students' knowledge and skills through an active combination of the eyes, heart, head, and hands. In addition, LKP Imam Mandiri also applies peer learning so that students can easily accept knowledge and skills deepened through internship activities. With certified instructors, students are always encouraged to be able to innovate and adapt to developments in the era of makeup.